Digitalization for Sustainable Development of Small Towns in Russia - Guzhavina Tatiana А. (European Journal of Sustainable Development, 2021)
Digitalization has become a significant trend in the development of modern humanity. The pandemic has accelerated the digitalization of most countries. They contribute to the development of new practices, open up new opportunities for communication. They also require certain skills and competencies, education. But digital environment affects people in different ways. It creates new problems and restrictions, increases risks, including increasing social inequalities. It can expand access to information, include a person in the global space, but it can also limit the world to the diagonal of a digital device. It is important to understand how the population is ready for these changes, what real opportunities it has. The digital environment is emerging in modern cities, where inclusion in it is faster. Ahead are megacities, industrial and administrative centers. But almost two thirds of the cities are small towns, where one fourth of the population of Russia lives. What are the opportunities for digitalization for the population of small towns, what are the restrictions for residents to be included in the digital space. The purpose of our study is to assess the state of digital competence of the population of small towns in the Russian Federation on the basis of their self-assessment of their readiness to function in a digital environment. The empirical basis of the study was the results of a survey conducted among the urban population of the Vologda region on a representative sample with quotas by gender and age. The study showed that there are problems in the development of the necessary competencies by residents of small towns to use the digital space.